PENINGKATAN PRODUKSI TANAMAN KEDELAI (Glycine max L.) DENGAN PEMBERIAN PUPUK TSP DAN PUPUK HAYATI FENG SHOU - Alridiwirsah ,; Sri Utami; Dwi Elisda Wulandari (AGRIUM: Jurnal Ilmu Pertanian, 2011)
AbstractThis study aims to determine the increase in production of soybean (Glycine max L.) with provision of fertilizers and fertilizer TSP Feng Shou and their interactions using Randomized Design Group (RAK) factorial with two factors studied, namely: TSP fertilizer (T) which consists of three extent that to = Without Giving, T1 = 36 g / plant and T2 = 48 g / plant fertilizer while Feng Shou (F) which consists of 3 standard are: F0 = Without Giving, F1 = 8 ml / plot and F2 = 16 ml / plot. TSP fertilizer as the first factor and fertilizer Feng Shou as a second factor.Key words: Production, Soybean, fertilizer TSP, Feng Shou